Evolución histórica de la función social de las bibliotecas públicas - Fernández Abad, Francisco Javier (Revista General de Información y Documentación, 2007)
Public libraries have one specific mission with the society since their same origin. But this mission have gone changing according to the history and men’s development. Public libraries have passed to be a tool of the power in their beginning, until to be a documental institution that to rich the education, the culture and men’s development at today.